STRATEGI MSDM DALAM MENCAPAI KEUNGGULAN BERSAING - Ganjar Garibaldi (Center for Economic Studies Universitas Katolik Parahyangan, 2006)
The main objective of this research is to study and analyze the roles of human resource management strategic on competitive advantage. The library research was used in doing and making this paper. The results of this library research indicate that the implementation of strategic human resource management consists of competitive advantage. Overall, the result of research indicates that the Strategic of human resource management strategies have effectively and based significantly role in the competitive advantage.